2013
DOI: 10.5812/hepatmon.6712
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Mutational Patterns in Hepatitis B Virus (HBV) Reverse Transcriptase Proteins From Iranian Treatment-Naïve Chronic HBV Patients

Abstract: BackgroundImmunomodulators and Nucleotide analogues have been used globally for the dealing of chronic hepatitis B virus (HBV) infection. However, the development of drug resistance is a major limitation to their long-term effectiveness.ObjectivesThe aim of this study was to characterize the hepatitis B virus reverse transcriptase (RT) protein variations among Iranian chronic HBV carriers who did not receive any antiviral treatments.Materials and MethodsHepatitis B virus partial RT genes from 325 chronic in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The rare S78T mutation also observed in one patient can lead to tenofovir resistance (45). Other mutation that observed in this study was L91I which reported as an Entecavir, lamivudine -related resistance mutation (46, 47). …”
Section: Discussionmentioning
confidence: 49%
“…The rare S78T mutation also observed in one patient can lead to tenofovir resistance (45). Other mutation that observed in this study was L91I which reported as an Entecavir, lamivudine -related resistance mutation (46, 47). …”
Section: Discussionmentioning
confidence: 49%
“…The truncated S protein that results from this stop codon may have a transactivating effect on several proteins in host cells [Lai and Yeh, ; Yeh, ]. There are discrepancies in the surveys regarding the antiviral resistant variants among treatment‐naïve Iranian HBV carriers in different studies [Amini‐Bavil‐Olyaee et al, ; Mahabadi et al, ]. Although two strains carried a stop codon at HBsAg, HBsAg was still detectable in those two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that in comparison with other studies, the mutations related to drug resistance in Iranian treatmentnaïve chronic HBV patients were higher. Hence, in order to attain an excellent regimen option, they suggested that chronic HBV patients should be monitored closely before the start of therapy (31).…”
Section: Discussionmentioning
confidence: 99%